sj-docx-1-hol-10.1177_09596836221138336 – Supplemental material for Synchronous change in the intensified millet cultivation and ecological environment from the early to middle Holocene on the Inner Mongolia Plateau, northern China - Keliang Zhao; Huiping Wei; Zhanhu Zhao; Yaping Zhang; Wenqing Liu; Jian Wang; Guanhan Chen; Hui Shen; Hua Du; Peng Cheng; Shan Chen; Peter Weiming Jia; et al. (SAGE Journals, 2022)
Supplemental material, sj-docx-1-hol-10.1177_09596836221138336 for Synchronous change in the intensified millet cultivation and ecological environment from the early to middle Holocene on the Inner Mongolia Plateau, northern China by Keliang Zhao, Huiping Wei, Zhanhu Zhao, Yaping Zhang, Wenqing Liu, Jian Wang, Guanhan Chen, Hui Shen, Hua Du, Peng Cheng, Shan Chen, Peter Weiming Jia, Xinying Zhou and Xiaoqiang Li in The Holocene
Keywords: Geography; History